RORα and REV-ERBα are Associated With Clinicopathological Parameters and are Independent Biomarkers of Prognosis in Gastric Cancer - Xiaoshan Wang MM; Ru Jia MM; Ke Chen MM; Jingjing Wang MM; Kai Jiang MM; Zhengguang Wang MD (Technology in Cancer Research & Treatment, 2021)
Retinoid-related orphan receptor alpha (RORα) and nuclear receptor subfamily 1 group D member 1 (REV-ERBα) play critical roles in many human cancers. Whether RORα and REV-ERBα expression levels are associated with clinical characteristics are poorly understood, and they may be independent predictors of overall survival (OS) and progression-free survival (PFS) in gastric cancer (GC). This study aimed to investigate the correlation of RORα and REV-ERBα expression levels with clinicopathological parameters, OS, and PFS in GC. Immunohistochemistry and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) were employed to assess the expression levels of RORα and REV-ERBα, which were downregulated in GC tissues compared with normal gastric tissues ( P  < .001; P  < .001) and were associated with several clinicopathological parameters, including histological grade ( P  = .032; P  < .001), preoperative carcinoembryonic antigen (CEA) levels ( P  = .004; P  < .001), and tumor-node-metastasis (TNM) stage ( P  = .015; P  < .001). Additionally, low RORα and REV-ERBα expression levels were associated with poor OS and PFS in GC patients, respectively ( P  < .001; P  = .001). Furthermore, univariate Cox regression model analysis showed that histological grade ( P  < .001; P  < .001), preoperative CEA levels ( P  < .001; P  = .001), TNM stage ( P  < .001; P  < .001), lymph node metastasis ( P  = .002; P  = .002), RORα expression levels ( P  = .001; P  < .001), and REV-ERBα expression levels ( P  < .001; P  = .001) were associated with OS and PFS in GC. Multivariate Cox regression model analysis indicated that RORα expression levels and REV-ERBα expression levels are independent factors of OS and PFS in GC. Besides, RORα and REV-ERBα expression may be positively correlated (χ 2  = 6.835; P  = .009), and GC patients with both high RORα and REV-ERBα expression levels had the best prognosis. In conclusion, RORα and REV-ERBα may coparticipate in tumor activities and show potential to estimate the prognosis of GC.